FEATURES OF DESIGN OF THE LED TAIL LIGHTS FOR PASSENGER CARS - Ihnatov, H. S. (Science and Transport Progress, 2005)
In work the description and results of tests of a design of light-emitting diode rear lights of carriages is resulted. Originality and reliability of a function chart of rear lights promotes a safety increase of movement.